Multifocal breast cancers are more prevalent in BRCA2 versus BRCA1 mutation carriers. (5th February 2020) - McCrorie, Alan D; Ashfield, Susannah; Begley, Aislinn; Mcilmunn, Colin; Morrison, Patrick J; Boyd, Clinton; Eccles, Bryony; Greville‐Heygate, Stephanie; Copson, Ellen R; Cutress, Ramsey I; Eccles, Diana M; Savage, Kienan I; et al.
Abstract: Multifocal (MF)/multicentric (MC) breast cancer is generally considered to be where two or more breast tumours are present within the same breast, and is seen in ~10% of breast cancer cases. This study investigates the prevalence of multifocality/multicentricity in a cohort of BRCA1/2 mutation carriers with breast cancer from Northern Ireland via cross‐sectional analysis. Data from 211 women with BRCA1/2 mutations ( BRCA1 ‐91, BRCA2 ‐120) and breast cancer were collected including age, tumour focality, size, type, grade and receptor profile. The prevalence of multifocality/multicentricity within this group was 25% but, within subgroups, prevalence amongst BRCA2 carriers was more than double that of BRCA1 carriers ( p = 0.001). Women affected by MF/MC tumours had proportionately higher oestrogen receptor positivity ( p = 0.001) and lower triple negativity ( p = 0.004). These observations are likely to be driven by the higher BRCA2 mutation prevalence observed within this cohort. The odds of a BRCA2 carrier developing MF/MC cancer were almost four‐fold higher than a BRCA1 carrier (odds ratio: 3.71, CI: 1.77–7.78, p = 0.001). These findings were subsequently validated in a second, large independent cohort of patients with BRCA ‐associated breast cancers from a UK‐wide multicentre study. This confirmed a significantly higher prevalence of MF/MC tumours amongst BRCA2 mutation carriers compared with BRCA1 mutation carriers. This has important implications for clinicians involved in the treatment of BRCA2 ‐associated breast cancer, both in the diagnostic process, in ensuring that tumour focality is adequately assessed to facilitate treatment decision‐making, and for breast surgeons, particularly if breast conserving surgery is being considered as a treatment option for these patients.